Tic20 forms a channel independent of Tic110 in chloroplasts - Kovács-Bogdán, Erika (BioMed Central, 2011)
BACKGROUND: The Tic complex (Translocon at the inner envelope membrane of chloroplasts) mediates the translocation of nuclear encoded chloroplast proteins across the inner envelope membrane. Tic110 forms one prominent protein translocation channel. Additionally, Tic20, another subunit of the complex, was proposed to form a protein import channel - either together with or independent of Tic110. However, no experimental evidence for Tic20 channel activity has been provided so far. RESULTS: We performed a comprehensive biochemical and electrophysiological study to characterize Tic20 in more detail and to gain a deeper insight into its potential role in protein import into chloroplasts. Firstly, we compared transcript and protein levels of Tic20 and Tic110 in both Pisum sativum and Arabidopsis thaliana. We found the Tic20 protein to be generally less abundant, which was particularly pronounced in Arabidopsis. Secondly, we demonstrated that Tic20 forms a complex larger than 700 kilodalton in the inner envelope membrane, which is clearly separate from Tic110, migrating as a dimer at about 250 kilodalton. Thirdly, we defined the topology of Tic20 in the inner envelope, and found its N- and C-termini to be oriented towards the stromal side. Finally, we successfully reconstituted overexpressed and purified full-length Tic20 into liposomes. Using these Tic20-proteoliposomes, we could demonstrate for the first time that Tic20 can independently form a cation selective channel in vitro. CONCLUSIONS: The presented data provide first biochemical evidence to the notion that Tic20 can act as a channel protein within the chloroplast import translocon complex. However, the very low abundance of Tic20 in the inner envelope membranes indicates that it cannot form a major protein translocation channel. Furthermore, the independent complex formation of Tic20 and Tic110 argues against a joint channel formation. Thus, based on the observed channel activity of Tic20 in proteoliposomes, we speculate that the chloroplast inner envelope contains multiple (at least two) translocation channels: Tic110 as the general translocation pore, whereas Tic20 could be responsible for translocation of a special subset of proteins.